PANDANGAN NINIK MAMAK TERHADAP RELASI GENDER DI DESA PULAU JAMBU KECAMATAN KUOK - Fitrah Herlinda (Marwah: Jurnal Perempuan, Agama dan Jender, 2016)
This paper aims to describe the view of NinikMamak about gender relations in the island village of Jambu sub district Kuok. Forms of this research is descriptive qualitative and data collection methods is indepth interviews. The results showed that the views of NinikMamak against women who play a role in the public sphere is not contrary to the customs and culture because there is no fixed rule in tradition about what work is done and is not appropriate for women and men. However, women can not be leaving responsibilities as wives and mothers even though women are the backbone of the family. In general shift among the view of NinikMamak is encouraging, but in substantive, views NinikMamak still experienced gender bias. It is suggested to governments and organizations engaged in gender to further improve socialization or education on gender equality among Ninik Mamak that their understanding of the problems of women do not experienced gender bias.